Bycie dziecka w Polsce „dobrej zmiany”– między Konwencją o Prawach Dziecka a rzeczywistością - Małgorzata Dagiel; Małgorzata Kowalik-Olubińska (Problemy Wczesnej Edukacji)
The aim of the authors is to show the situation of the child in contemporary Poland at a time of a policy of ‘good change’ viewed through the lens of children’s rights guaranteed by the Convention on the Rights of the Child. The authors analysed a discourse of the Ombudsmen for Children’s interventions in order to reconstruct the image of being of the child in a new socio-political reality in Poland. The analysis shows the disagreement between the assumptions of the pro-family state policy and the situation of the child in Poland. Concern about child welfare presented by the governmental authorities is apparent and insufficient, which adversely affects children’s well-being and the quality of their lives.